Synthesis of Cellulose Acetate-Polystyrene Membrane Composites from Pineapple Peel Wastes for Methylene Blue Removal - Firdaus, Irvan Maulana; Febiyanto, Febiyanto; Fitriany, Try; Zulhidayah, Lely Zikri; Septiarini, Dyah Ayu; Wibowo, Oto Dwi (Al-Kimia, 2019)
The cellulose acetate-polystyrene or CA-PS composite membrane from pineapple peel waste for methylene blue removal has been conducted. The steps were nata de pina preparation, cellulose acetylation process, preparation, and characterization of CA-PS composite membrane. The CA-PS composite membrane was characterized using Fourier Transform Infrared (FT-IR), Scanning Electron Microscopy (SEM), tensile and strain examination, respectively. The as-synthesized CA-PS composite membrane has the characteristic of rejection ability was about 29.96% with the pore size, membrane modulus, stress and strain were 1.9 μm, 12.48 MPa, 31.91 MPa, and 2.55, respectively. In this research, CA-PS composite membrane from pineapple peel waste was successfully removed the methylene blue dye even needs improvement to enhance its capability in rejection efficiency as same as membrane characteristics.